(untitled) (Journal of Civil Engineering Researchers, 2022)
Many of the old bridges in northern Iran, which are often more than 50 years old, are made of steel trusses. The superstructure of these bridges usually consists of two simple and parallel trusses that increase lateral stability, the upper part of these two trusses are connected using bracing elements. In some truss bridges such as the Sardabroud-Chalous bridge, the transverse brace has been removed due to the small length of the span (about 31 meters). These types of trusses that do not have transverse restraints in the upper part are called pony trusses, which have less lateral resistance due to the removal of transverse restraints. On December 25, 2009, while the trailer was passing, a steel cargo weighing about 10 tons was released from the trailer floor and thrown towards one of the vertical elements of the truss. The impact of this heavy object causes the failure of this member and the subsequent failure of the adjacent members, which eventually leads to the collapse of the entire structure. In this paper, the progressive failure mechanism of Sardabrood Bridge will be studied using ABAQUS software. The results of sensitivity analysis and Downstream analysis show that except for zero force elements, other vertical and oblique elements have significant sensitivity that should be prevented from being damaged. Interestingly, at the moment of failure and after the failure, the alternative route is the force distribution, which is mainly the forces trying to cross the pressure rim, but small deformations in a chain led to large deformations and caused the progressive failure, which destroyed the bridge in 0.7 seconds.